GERAKAN SIAP MENIKAH (GSM) EFFORTS TO REDUCE RATE OF EARLY MARRIAGE "MORE PREPARED, MORE UNEARLY THE MARRIAGE" - Astuti, Riqi; Gemi, Gede Sangu; Budiyanto, Ridwan (Program Kreativitas Mahasiswa - Pengabdian Kepada Masyarakat, 2014)
Indonesia was the 37th by the number of early marriages in the world and was ranked second in ASEAN (UNDESA, 2011). Gunungkidul ranks is the highest of early marriage rate in the DIY province. In 2009 an application for early marriage dispensation for women under 16 years old and men under 19 years old reach 80, That number continues to increase each year, until 2011 as many as 145 applicants(krjogja.com). Parents point of view who want their children to marry early often occur in Tepus, Gunungkidul, Yogyakarta. Until now, there has been no movement or trainings of the steps to prepare and manage a family. Through the creativity of the student program "Gerakan Siap Menikah (GSM) in Blekonang, Tepus, Gunungkidul is expected to provide knowledge and concrete solutions to overcome this. This program begins with dissemination for villagers related to the aims and objectives, the establishment of the GSM community with young people as the administrator, GSM organizational management training (in collaboration with Quantum Remaja), the work program of the GSM, namely; launching of GSM community, marriage preparation and dissemination danger of early marriage (in collaboration with BKKBN), training parenting (in collaboration with PLKB), and skills development. Indicators of the achievement of this program are (1) The establishmentÂ  a community board of GSM with 15 people (2) The occurrence of an increased understanding and awareness of the importance of the preparations of family management and the risk of early marriage. The percentage of understanding Â marriage preparation or housekeeping increase from 40% with the criteria âEnoughâ to 79% with the criteria very well. Understanding Â the dangers of early marriage increase from 69% to 73%.Â Keyword: early marriage, community, family management